S.F. VOTES ON PLAN, SMOKE, ENGLISH. (Tufts Archival Research Center, 2007)
Marginalia; News article on San Francisco ballot propositions, including measures dealing with development, smoking, and language. Lists proponents and opponents to the propositions. Discusses Proposition P which would restrict smoking in the workplace.